A combination of three-dimensional printing and computer-assisted virtual surgical procedure for preoperative planning of acetabular fracture reduction. Issue 10 (October 2016) - Zeng, Canjun; Xing, Weirong; Wu, Zhanglin; Huang, Huajun; Huang, Wenhua
Abstract: Objective: Treatment of acetabular fractures remains one of the most challenging tasks that orthopaedic surgeons face. An accurate assessment of the injuries and preoperative planning are essential for an excellent reduction. The purpose of this study was to evaluate the feasibility, accuracy and effectiveness of performing 3D printing technology and computer-assisted virtual surgical procedures for preoperative planning in acetabular fractures. We hypothesised that more accurate preoperative planning using 3D printing models will reduce the operation time and significantly improve the outcome of acetabular fracture repair. Methods: Ten patients with acetabular fractures were recruited prospectively and examined by CT scanning. A 3-D model of each acetabular fracture was reconstructed with MIMICS14.0 software from the DICOM file of the CT data. Bone fragments were moved and rotated to simulate fracture reduction and restore the pelvic integrity with virtual fixation. The computer-assisted 3D image of the reduced acetabula was printed for surgery simulation and plate pre-bending. The postoperative CT scan was performed to compare the consistency of the preoperative planning with the surgical implants by 3D-superimposition in MIMICS14.0, and evaluated by Matta's method. Results: Computer-based pre-operations were precisely mimicked and consistent with the actual operations in all cases. The pre-bent fixation plates had an anatomical shape specifically fit to the individual pelvis without further bending or adjustment at the time of surgery and fracture reductions were significantly improved. Seven out of 10 patients had a displacement of fracture reduction of less than 1 mm; 3 cases had a displacement of fracture reduction between 1 and 2 mm. Conclusions: The 3D printing technology combined with virtual surgery for acetabular fractures is feasible, accurate, and effective leading to improved patient-specific preoperative planning and outcome of real surgery. The results provide useful technical tips in planning pelvic surgeries.